2018
DOI: 10.1371/journal.pone.0194780
|View full text |Cite
|
Sign up to set email alerts
|

S-allylmercapto-N-acetylcysteine protects against oxidative stress and extends lifespan in Caenorhabditis elegans

Abstract: S-allylmercapto-N-acetylcysteine (ASSNAC) was shown in our previous study to activate Nrf2-mediated processes and increase glutathione level and resistance to oxidative stress in cultured endothelial cells. In this study, we explored the antioxidant protective effect of ASSNAC in Caenorhabditis elegans (C. elegans). Treatment of gst-4 reporter strain (CL2166) with increasing concentrations of ASSNAC (0.2 to 20 mM) for 24 hours and with ASSNAC (10 mM) for various time periods demonstrated a significant concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This ASSNAC-induced Nrf2 activation increased the expression of phase II detoxifying enzymes, including the cystine transporter (xCT), which provides cells with free cysteine as a substrate for glutathione biosynthesis. Thus, ASSNAC dual anti-oxidant activity includes increased cellular availability of cysteine (via released NAC and up-regulated cysteine transporter activity) and up-regulated phase II-induced enzymes for glutathione biosynthesis, both leading to significant increase in glutathione cellular level, resulting in significant augmentation of cells [20] and of the entire organism [21] resistance to oxidative stress. Indeed, our further study demonstrated a protective role for ASSNAC against oxidative stress, as it attenuated the clinical symptoms in experimental autoimmune encephalomyelitis (EAE), which serves as a mouse model for multiple sclerosis [22].…”
Section: Introductionmentioning
confidence: 99%
“…This ASSNAC-induced Nrf2 activation increased the expression of phase II detoxifying enzymes, including the cystine transporter (xCT), which provides cells with free cysteine as a substrate for glutathione biosynthesis. Thus, ASSNAC dual anti-oxidant activity includes increased cellular availability of cysteine (via released NAC and up-regulated cysteine transporter activity) and up-regulated phase II-induced enzymes for glutathione biosynthesis, both leading to significant increase in glutathione cellular level, resulting in significant augmentation of cells [20] and of the entire organism [21] resistance to oxidative stress. Indeed, our further study demonstrated a protective role for ASSNAC against oxidative stress, as it attenuated the clinical symptoms in experimental autoimmune encephalomyelitis (EAE), which serves as a mouse model for multiple sclerosis [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, gst-4 is related to glutathione metabolism, and gst-7 is related to innate immunity. They are all homologous to human hematopoietic prostaglandin D synthase gene [ 42 , 43 ]. gst-10 is orthologous to human glutathione S-transferase pi 1, which plays an important role in the regulation of life span and thermal acclimatization [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lifespan assays were performed using regular NGM plates seeded with OP50 at 20°C, as previously described, but with some alterations [77]. Briefly, gravid adults were bleached three consecutive times prior to the assays.…”
Section: Methodsmentioning
confidence: 99%